Diphenylmorpholine CMPO: Synthesis, coordination behavior and extraction studies of actinides. (15th February 2018) - Das, Dhrubajyoti; Sivaramakrishna, Akella; Gopakumar, Gopinadhanpillai; Brahmmananda Rao, C.V.S.; Sivaraman, N.; Vijayakrishna, Kari
Graphical abstract: Diphenylmorpholine carbamoylmethyl phosphine oxide ( L1 ) and diphenyl- N, N -diethyl carbamoylmethyl phosphine oxide ( L2 ) were synthesized and characterized. For these two ligands L1 and L2, the distribution values of Th(IV) is almost three fold higher than the DU(VI) indicating selectivity of these ligands towards thorium over uranium. Abstract: Carbamoylmethyl phosphine oxide (CMPO) derivatives are well known ligands in the separation and extraction of trivalent lanthanides and actinides from nuclear waste. The substituents of CMPO play major role in their selectivity and extractability. We report the synthesis and characterization of diphenylmorpholine carbamoylmethyl phosphine oxide (DPMCMPO) ( L1 ) and diphenyl- N, N -diethyl carbamoylmethyl phosphine oxide (DPDECMPO) ( L2 ) using various spectroscopic techniques, such as FT-IR, 1 H, 13 C, and 31 P NMR. The molecular structure of DPMCMPO is confirmed by single crystal XRD analysis. The present study aims to understand the influence of substituents on 'N' atom of L1 (morpholine based DPMCMPO) and L2 (diethyl substituted DPDECMPO) ligands for the extraction of some selected actinide ions such as Th(IV), U(VI) and Am(III). The geometry and electronic structure of these ligands and their respective complexes with Th(NO3 )4 and UO2 (NO3 )2 are further explored using density functional theory (DFT) calculations. The employed ligands ( L1 and L2 ) show greater distribution values for Th(IV) over U(VI), due to strong "ligand-Th" complexation ability as suggested by DFT calculations.